'I have seen Königsberg burning': Philosophical anthropology and the responsiveness of historical experience. (March 2014) - Wentzer, Thomas Schwarz
It is December 1944 in East Prussia, and a German mother with the four youngest of her 13 children is fleeing from the Red Army. Some 30 years later one of her sons talks about his memories, using the phrase: 'I have seen Königsberg burning' – what a sentence. The city of Immanuel Kant, the most important philosopher of the German Enlightenment and an icon in human moral thought, is burning down. But then again, is it legitimate to take this symbolic interpretation as the proper meaning of this sentence? Drawing on Gadamer's philosophical hermeneutics I present an account of historical experience, exemplifying the experiential and existential character of human life. Historical experience arises subsequently, in retrospection, in response to a demand without access to the original event that encompassed the essence or the real content to be experienced. Hence the notion of historical experience has to be deconstructed (against historical realism or historicism) and defended (against constructivism and structuralism) at the very same time. The concept of responsiveness is introduced in order to encompass the paradox contained in this agenda, in particular the need to think of the human as a responsive being.